MDLab: AI frameworks for carbon capture and battery materials - Elmegreen, Bruce; Hamann, Hendrik F.; Wunsch, Benjamin; Van Kessel, Theodore; Luan, Binquan; Elengikal, Tonia; Steiner, Mathias; Neumann Barros Ferreira, Rodrigo; Ohta, Ricardo Luis; Oliveira, Felipe Lopes; McDonagh, James L.; O’Conchuir, Breanndan; et al. (Frontiers in Environmental Science, 2023)
There is a growing urgency to discover better materials that capture CO2 from air and improve battery performance. An important step is to search large databases of materials properties to find examples that resemble known carbon capture agents or electrolytes and then test them for effectiveness. This paper describes novel computational tools for accelerated discovery of solvents, nano-porous materials, and electrolytes. These tools have produced interesting results so far, such as the identification of a relatively isolated location in amine configuration space for the solvents with known carbon capture use, and the demonstration of an end-to-end simulation and process model for carbon capture in MOFs.